RANCANG BANGUN SISTEM INFORMASI PEMESANAN MAKANAN BERBASIS WEB PADA CAFE SURABIKU - Saputri, Zia Rizki; Oktavia, Anzani Nur; Ramdhani, Lis Saumi; Suherman, Acep (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
Café is a place that serves drinks and food orders, café is also one of the centers of social interaction where people can gather, talk, write, read, joke, or just fill their time. Ordering is an activity carried out by consumers before buying. To realize customer satisfaction, the company must have a good ordering system. The research method used in this study uses data collection methods, namely by observation, interviews, and literature. While for software development using the waterfall method. At this time the Surabiku Cafe has difficulties in serving orders and still uses records that have not been computerized or still use conventional systems. Where the buyer has to wait too long to order food, besides that the waiter also has difficulty in manually recording orders using paper. Manually recording orders is less efficient in terms of time. So to realize customer satisfaction in food ordering, a web-based food ordering information system design was developed using PHP and Mysql. Keywords: Ordering, Information System, Café, Web